Pengetahuan tentang HIV berhubungan dengan Ketertarikan Mengikuti Voluntary Counselling and Testing pada Pasangan Usia Subur: Penelitian Observasional - Hutomo, Wahyuni Maria Prasetyo; Pramukti, Iqbal; Sari, Sheizi Prista (Poltekkes Kemenkes Kendari, 2023)
Every year there are 5,100 new Human Immunodeficiency Virus (HIV) infections among housewives, 33% of whom are infected by their partners who engage in risky sexual behavior. Therefore, utilization of HIV screening through voluntary counselling and testing (VCT) services is important especially for those with high risk. This study was conducted to determine the relationship between knowledge of couples of childbearing age in Garut Regency, especially in Ciwalen Village with interest in participating in HIV screening through VCT. This study is a quantitative study with a cross sectional approach. Data collection was carried out on May 2-June 2, 2023 and was located in one of the Ciwalen Villages in Garut Regency, West Java. The study population was one of the couples of childbearing age who lived permanently in one of the villages in Garut Regency with purposive sampling technique totaling 121 married men or women of childbearing age. Data collection was conducted using a questionnaire that included information on respondent characteristics, questions related to interest in attending VCT combined with the HIV-KQ-18 questionnaire to assess respondents' knowledge about HIV/AIDS. Data were collected using a questionnaire that included information on respondents' characteristics, questions related to interest in attending VCT combined with the HIV-KQ-18 questionnaire to assess respondents' knowledge about HIV/AIDS. Data were analyzed using SPSS software (Version 21), frequency distribution analysis and chi-square test. The results showed that the majority of couples of childbearing age (78 people, 64.5%) had poor knowledge about HIV/AIDS and only a few (26.4%) of them were interested in following HIV screening through VCT. Interest in VCT was more prevalent among couples of childbearing age who had good knowledge about HIV/AIDS (P < 0.05). To increase the interest of couples of childbearing age in HIV screening, efforts should be made to increase their knowledge about HIV/AIDS.